BANK SAMPAH SEBAGAI INSTRUMEN PEMBERDAYAAN DESA DALAM MEWUJUDKAN LINGKUNGAN BERSIH DAN EKONOMI SIRKULAR - Rifky Lana Rahardian; Andi Pratama; Siti Azizah (Yayasan Baitul Hikmah al-Zain, 2025)
This community service program aims to empower village communities through the establishment of waste banks as a solution for sustainable waste management. The background of the activity is the increasing volume of unmanaged household waste, which has led to environmental and health problems in the village. The waste bank was chosen as an instrument because it can integrate environmental, social, and economic aspects simultaneously. The service method is carried out using a participatory approach, including outreach, technical training on waste sorting, waste bank administration management, and mentoring community groups. The results of the activity show an increase in community awareness of the importance of waste management starting from the household level. The community has become accustomed to sorting organic and inorganic waste and submitting it to the waste bank. The collected waste is then processed or resold, generating economic value for the community. In addition to impacting environmental cleanliness, this program also creates a circular economic system in the village, where waste is viewed as a resource, not a burden. The waste bank has proven to be an effective instrument for empowering village communities, strengthening community participation, and supporting environmentally friendly sustainable development.